The Role of Information Security in the Business Processes - Dombora, Sándor; Michelberger, Pál (International Journal of Engineering and Management Sciences, 2016)
Information security (namely, confidentiality, integrity, and availability of business-related data) is an issue which companies attach increasing importance nowadays. This is, however, not a self-centred goal to achieve, but an (additional) means businesses use to work towards security in their overall operations. In addition to briefly presenting two case studies on information security practices, this paper offers a survey of terms and management practices linked with process security. Business continuity planning and risk management techniques - as outlined here in connection with information protection controls - may cover all business processes at any company.